Hot roller embossing of multi-dimensional microstructures using elastomeric molds - Zhong, Zhaowei (2020)
In this work, we investigated how elastomeric mold properties could affect the final replication accuracy in hot roller embossing. Amorphous polyethylene terephthalate was used as the polymer substrate. It was discovered that for dense features, the elastomeric mold provided better replication results compared to a metal mold. The experimental results revealed that embossing with larger pitch sizes such as 300 and 400 µm achieved better replication accuracy than that with smaller pitch sizes such as 100 and 200 µm. The side-wall surface areas of the features on the mold affected the embossing process, resulting in different degrees of replication accuracy.